Influence of Water Table Fluctuation on Natural Source Zone Depletion in Hydrocarbon Contaminated Subsurface Environments - Ismail, Reem; Shafieiyoun, Saeid; Al-Raoush, Riyadh I. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Most of the prediction theories regarding dissolution of organic contaminants in the subsurface systems have been proposed based on the static water conditions and the influence of water fluctuations on mass removal requires further investigations. In this study, it was intended to investigate the effects of water table fluctuations on biogeochemical properties of the contaminated soil at the smear zone between the vadose zone and the groundwater table. An automated 60 cm soil column system was developed and connected to a hydrostatic equilibrium reservoir to impose the water regime by using a multi-channel pump. Four homogenized hydrocarbon contaminated soil columns were constructed and two of them were fully saturated and remained under static water conditions while another two columns were operated under water table fluctuations between the soil surface and 40 cm below it. The experiments were run for 150 days and relevant geochemical indicators as well as dissolved phase concentrations were analyzed at 30 and 50 cm below the soil surface in all columns. The results indicated significant difference in terms of biodegradation effectiveness between the smear zones exposed to static and water table fluctuation conditions. This presentation will provide an overview of the experimental approach, mass removal efficiency, and key findings.